Possibilities of domestic railway engineering on the example of the Lastochka electric train - D. A. Plotnikova (Вестник университета)
The purpose of this article is to study the possibilities and assess the current state of the Russian railway engineering industry. The research paper analyzes the conditions conducive to the development of domestic railway engineering in the production of electric trains. The reasons for the demand for the Lastochka are described and the features of operation reflected, and the difficulties of localization of production listed. Due to domestic developments and various modifications, the electric train is recognized as universal and capable of a variety of operating conditions. The article focuses on the main competitive advantages of this train and the prospects for the development of the production of the Lastochkas in the Russian Federation within the framework of external sanctions pressure and a high level of uncertainty. The author reflects the advantages and disadvantages of replacing domestic electric trains as a part of import substitution with products from friendly or neutral countries. The study notes that in the near future the state will need to decide on a further policy of import substitution within the framework of risk assessment for the domestic economy.